GOTHIC FICTION: FIGURATIVE PLOT PARADIGM - Grosevych, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the theoretical generalization of the attributes of a poetic of gothic, in particular in the article is analyzed in details the figurative-motive and plot-compositional levels; is traced the evolution of the image of Devil; is identified the triune category − mystery / horror / suspense – as a genre constant of gothic fiction; is identified the road archetype; is analyzed the functionality of gothic, contrast as the dominant feature of the gothic paradigm; and also is grounded the philosophical doctrine of the theodicy as one of the fundamental basis of all gothic fiction.